Detection of resistance gene marker intl1 and antimicrobial resistance pattern of E. coli isolated from surgical site wound infection in Holy Family Red Crescent Medical College Hospital (Bangladesh Journal of Medical Microbiology, 2012)
This study was carried out to determine the presence of resistance gene intl1 in E. coli isolated from surgical site wound infection in Holy Family Red Crescent Medical College Hospital. A total of 90 samples were collected from the different wound sites of patients admitted in surgical ward. The most predominant organism was E. coli 48(53.33%); followed by S. aureus 23(25.56%) and Pseudomonas 12(13.33%). Most of the isolated strains of E. coli were multidrug resistant. 46(96%) strains were shown resistant to ampicillin and most potent drug against E. coli was found to be imepenem. The extended spectrum Beta-lactamase (ESBL) producing E. coli were 21(43.75%).The resistance gene marker intl1 was detected in 32(67%) E. coli isolates.DOI: http://dx.doi.org/10.3329/bjmm.v4i2.10827